The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.31018/jans.v13i1.2435
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of groundwater at Laksar Block, Haridwar in Uttarakhand, India using Water Quality Index: A case study

Abstract: Urbanization and industrialization enhance the degradation of the groundwater quality due to the discharge of domestic and industrial effluents in the aquatic bodies or on the surface of ground either in treated or untreated form. Therefore, the present study was carried out to assess the groundwater quality at the Laksar block of district Haridwar in Uttarakhand. Groundwater samples (SS-1-10) were collected from the hand pumps of the study area. The sampling site (SS-1) was taken as control. The distance of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, the EWQI value is the highest in the southwest of the study area, showing a trend of deterioration of groundwater water quality. As the assessment results of groundwater quality showed that the water quality was excellent, it was considered that the groundwater quality in the study area was very good, and the influence of natural filtration should be greater than that of human factors [42]. First of all, cation alternating adsorption leads to the gradual increase of Na concentration in the direction of groundwater flow in the study area.…”
Section: Discussionmentioning
confidence: 94%
“…However, the EWQI value is the highest in the southwest of the study area, showing a trend of deterioration of groundwater water quality. As the assessment results of groundwater quality showed that the water quality was excellent, it was considered that the groundwater quality in the study area was very good, and the influence of natural filtration should be greater than that of human factors [42]. First of all, cation alternating adsorption leads to the gradual increase of Na concentration in the direction of groundwater flow in the study area.…”
Section: Discussionmentioning
confidence: 94%
“…According to the World Health Organization (WHO), in 2017, more than 80% of all human infections were waterborne. Because groundwater is polluted, ensuring its safety is challenging Bhutiani et al, 2021). An appropriate analysis of the features of groundwater reservoirs is necessary to establish a sustainable exploitation of groundwater resources for further growth and requirements because there are many elements that might affect groundwater quality (Carrera-Hernandez and Gaskin, 2006;Chenini and Ben, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater is a very important component of the human life support system and it is required for drinking, household, industrial and agricultural uses (Bhutiani et al, 2021a;Bhutiani et al, 2021b;Ruhela et al, 2021).The groundwater quality is serious matter in arid and semi-arid areas, which is dominated by irrigation practices. Quality of ground water is adversely affected by the diffuse contamination devising from intensive agricultural practices (Bhutiani et al, 2019;Ruhela et al, 2022;Saidi et al, 2009).Groundwater has been a major and consistent source of drinking and irrigation for a wide range of users (Afzali et al, 2014).…”
Section: Introductionmentioning
confidence: 99%